Research Progress and Prospect of Nanoplatforms for Treatment of Oral Cancer - Zhao, Zhilong; Li, Dan; Wu, Ziqi; Wang, Qihui; Ma, Zhangyu; Zhang, Congxiao (Frontiers in Pharmacology, 2020)
Oral cancer refers to malignant tumors associated with high morbidity and mortality; oral squamous cell carcinoma accounts for the majority of cases. It is an important part of head and neck, and oral cancer is one of the six most common cancers in the world. At present, the traditional treatment methods for oral cancer include surgery, radiation therapy, and chemotherapy. However, these methods have many disadvantages. In recent years, nanomedicine, the delivery of drugs through nanoplatforms for the treatment of cancer, has become a substitutive therapy. The use of nanoplatforms can reduce the degradation of the drug in the body, and accurately deliver it to the tumor site. This minimizes the distribution of the drug to other organs, thereby reducing its toxicity and allowing higher drug concentration at the tumor site. This review presents the latest developments in drug delivery systems based on various types of nanoplatforms, and discusses the future prospects of nanoplatforms for oral cancer therapies.